2022
DOI: 10.7150/jca.71925
|View full text |Cite
|
Sign up to set email alerts
|

Identification of circadian clock genes as regulators of immune infiltration in Hepatocellular Carcinoma

Abstract: Background: Multiple studies have reported that the immune system is under the control of a circadian clock, especially in cancers, but how circadian clock genes shape tumor immune cell infiltration in hepatocellular carcinoma (HCC) remains unclear. Methods: The rhythmicity of circadian clock genes was investigated using the GETx database. The expression and methylation level of circadian clock genes in HCC and paracancerous was evaluated using the GETx and TCGA databases. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…NPAS2 is a circadian clock gene and has been reported to be a crucial regulator of tumorigenesis and immune infiltration. NPAS2 was identified as an oncogene in hepatocellular carcinoma and was related to infiltration of immune cells [ 23 ]. In accordance with our findings, increased expression of NPAS2 has been suggested to indicate poor survival in lung cancer [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…NPAS2 is a circadian clock gene and has been reported to be a crucial regulator of tumorigenesis and immune infiltration. NPAS2 was identified as an oncogene in hepatocellular carcinoma and was related to infiltration of immune cells [ 23 ]. In accordance with our findings, increased expression of NPAS2 has been suggested to indicate poor survival in lung cancer [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, NPAS2 was comprised in a five-gene signature (DKK1, CCL20, NPAS2, GNPNAT1 and MELTF) predicting prognosis (decreased overall survival rates and shorter progression-free survival) and immunotherapy response of lung adenocarcinoma patients [76]. Likewise, higher expression of the NPAS2 gene in tumor tissue was closely related with immune infiltration and overall survival of glioma patients [77] as well as to immune infiltration and poor prognosis in hepatocellular carcinoma patients [78,79]. In the setting of hepatocellular carcinogenesis, upregulation of NPAS2 expression, chiefly attributable to the downregulation of miR-199b-5p, was found capable to reprogram glucose metabolism through transcriptional activation of HIF-1α with upregulation of the glycolytic genes GLUT1, HK2, GPI, ALDOA, ENO2, PKM2 and MCT4 and downregulation of peroxisome proliferator-activated receptor gamma coactivator 1 alpha (PGC-1α) with subsequent reduced mitochondrial biogenesis [80].…”
Section: Npas2 In Cancer Onset and Progressionmentioning
confidence: 99%
“…Neuronal PAS domain protein2 ( NPAS2 ; also called MOP4), the largest circadian gene located on chromosome 2 at 2q11.2, has received much attention in recent years because of its multiple biological functions and diverse roles in various diseases, particularly tumorigenesis 11 . NPAS2 was identified as an oncogene in hepatocellular carcinoma, uterine corpus endometrial carcinoma, acute myeloid leukaemia, etc., which was correlated with the biofunctional activities of NPAS2 in regulating cellular behaviours such as cell proliferation, migration and apoptosis 12–14 . Epidemiological studies have indicated that genetic variants in NPAS2 gene are significantly associated with overall survival of patients with NSCLC, and NPAS2 polymorphisms are suggested to serve as an independent prognostic marker for NSCLC patients 15 .…”
Section: Introductionmentioning
confidence: 99%
“…11 NPAS2 was identified as an oncogene in hepatocellular carcinoma, uterine corpus endometrial carcinoma, acute myeloid leukaemia, etc., which was correlated with the biofunctional activities of NPAS2 in regulating cellular behaviours such as cell proliferation, migration and apoptosis. [12][13][14] Epidemiological studies have indicated that genetic variants in NPAS2 gene are significantly associated with overall survival of patients with NSCLC, and NPAS2 polymorphisms are suggested to serve as an independent prognostic marker for NSCLC patients. 15 Importantly, a recent article published in April 2023 verified the high expression level of NPAS2 in tumour tissues of LUAD patients and confirmed the oncogenic role of NPAS2 in LUAD for the first time, preliminarily emphasizing the importance of NPAS2 in LUAD tumorigenesis and progression.…”
Section: Introductionmentioning
confidence: 99%